Imaging the Morrow A Sandstone Using Shear Wave VSP Data, Postle Field, Oklahoma - Naser Tamimi; Thomas L. Davis (International Journal of Geophysics)
Morrow sandstones constitute important oil-producing reservoirs in the Anadarko Basin in the Mid-Continent Region of the USA. Characterization of the Morrow A sandstone reservoir in Postle Field, Texas County, Oklahoma, is challenging due to its small thickness, low acoustic impedance contrast with the surrounding Morrow shale, and lithological heterogeneity. Shear wave data have been documented as a promising solution for imaging the Morrow A sandstone. Vertical seismic profiling (VSP) offers the potential to enhance shear wave imaging of the thin heterogeneous Morrow A sandstone at Postle Field. The zero-offset VSP results confirm the advantages of shear wave over compressional wave in imaging the Morrow A sandstone. Also, the final shear wave VSP image shows that, applying the proposed processing flow, we are able to image the Morrow A sandstone where the thickness is as thin as 8.5 m.